BOSE AND RAMAN'S WAYS IN THE CLASSROOM: DEMONSTRATING THE DEATH OF PLANT CELLS AND MAGNETS - Sen, Subir K. (SCHOOL SCIENCE, 2013)
Living cells have specific structural organisation which in turn is a reflection of molecular configurations. Heating beyond a limit destroys that organisation causing death. Pasteurisation, which is the process of sterilisation by heat, has been possible because of this reason. Molecular configurations of most of the germ cells are damaged severely above a certain temperature. So the germ cells die.